Life Cycle Assessment - Hauschild, Michael Z.; Rosenbaum, Ralph K.; Olsen, Stig Irving (Springer, 2018)
It is an old observation that ‘What gets measured gets managed’, and that what is not measured or measurable runs the risk of being neglected. It is therefore important that we have tools for assessing the sustainability of our choices when we develop the technologies and systems that shall help us determine and meet the needs of the present generations in a way that does not compromise the ability of our descendants to meet their needs in the future. As you will learn from this book, we must take a life cycle perspective when we want to assess the sustainability of the solutions that lie in front of us. You will be presented with many examples of problem shifting where solutions that improve or solve a targeted problem unintentionally create other problems of environmental, economic or social nature somewhere else in the systems of processes and stakeholders affected by our choice. If we do not consider the totality of these systems in our analysis, we will fail to notice these unwanted consequences of our decision and we will not be able to take them into consideration. We also have to consider a broad range of potential impacts in our assessment, in fact all those is that the system can contribute to and that we consider relevant in the context of our decision-situation. Life Cycle Assessment, LCA, offers this totality—it analyses the whole life cycle of the system or product that is the object of the study and it covers a broad range of impacts for which it attempts to perform a quantitative assessment. The focus of LCA has mainly been on the environmental impacts although both social and economic impacts can be included as well. It is an important assessment tool as demonstrated by the central role that it has been given in the environmental regulation in many parts of the world and certified by its ISO standardization and the strong increase in its use over the last decades by companies from all trades and all over the world.
Theory and Practice